Balanço Orçamentário Estrutural, Receita Cíclica e Impulso Fiscal: uma análise das contas públicas do Estado de Goiás - Seixas, Flávio Henrique de Sarmento (2018)
This work on subnational public finances analyzes two important topics for the improvement of fiscal results: the adaptation and construction of Structural Budget Balances for the state entities with the determination of their respective results; and, later, the proposal of an adequate econometric model for the forecast of the total collection of state revenues, based on the ARMAX methodology. After examining in detail the public accounts of a federal unit, the State of Goiás, the methodology for the construction of a Structural Budget Balance was applied for the period 2003/2016, which will identify the genuine fiscal impulses arising from the discretionary actions of regional fiscal policy. The empirical strategy adopted was based on the established methodologies of the International Monetary Fund (IMF) and the Organization for Economic Cooperation and Development (OECD) and, with adaptations, one can obtain the Product Hiatus of the State of Goiás via the Hodrick-Prescott Filter (HP), and the Elasticity Revenue of the GOI GDP, via MQO and via the Kalman Filter. For quarterly data (56 quarters), the elasticity-revenue of the state product resulted in values consistent with those found in the literature: 1.2836 (OLS). By Kalman Filter, the results were: 1,719 for the total collection of state revenues and: ICMS, 2,765; ITCD: 6,387; Government Transfers: 0.216; IPVA: no valid template. The results indicated that the Cyclic Revenue in Goiás was positive in 2004, 2008 and in the period 2011-2014; being negative in 2003, 2006, 2009, and in the 2015/16 biennium, by any methodology adopted. As for the Structural Balance, except in the years 2003, 2009 (MQO and Kalman) and in the 2015/16 biennium (Kalman), the structural results were smaller than the conventional ones. In addition, for both methodologies, Goiás recorded expansionary fiscal momentum in 2004, 2010, 2012 and 2014, and contractionary momentum in the period 2005/2009, 2011, 2013, and 2015/16. According to the analyzes, long-term GDP reversed the growth trend in the first quarter of 2010 and could start a new cycle of growth in the second quarter of 2018, eight years later. The results obtained allow us to conclude that the methodology has been successfully applied to the Goiano case and that it can be adapted to the subnational units - which disclose quarterly GDP - contributing to improve national and subnational fiscal rules. As to the proposal of prediction models, among the four identified, the best presented MAPE of 1.7% for the year 2015, and identified the exogenous economic variable “Formal Employment Level” as significant.